2017
DOI: 10.1038/ismej.2016.184
|View full text |Cite
|
Sign up to set email alerts
|

Shift in fungal communities and associated enzyme activities along an age gradient of managed Pinus sylvestris stands

Abstract: Forestry reshapes ecosystems with respect to tree age structure, soil properties and vegetation composition. These changes are likely to be paralleled by shifts in microbial community composition with potential feedbacks on ecosystem functioning. Here, we assessed fungal communities across a chronosequence of managed Pinus sylvestris stands and investigated correlations between taxonomic composition and extracellular enzyme activities. Not surprisingly, clear-cutting had a negative effect on ectomycorrhizal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
189
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(229 citation statements)
references
References 60 publications
(81 reference statements)
23
189
5
Order By: Relevance
“…In the same study system as in the present study, Kyaschenko et al . () observed a succession in the mycorrhizal fungal community from dominance by Piloderma and Tylospora spp. in the younger stands to dominance by Cortinarius and Russula spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study system as in the present study, Kyaschenko et al . () observed a succession in the mycorrhizal fungal community from dominance by Piloderma and Tylospora spp. in the younger stands to dominance by Cortinarius and Russula spp.…”
Section: Discussionmentioning
confidence: 99%
“…There were highly significant differences in overall community structure of bacteria colonizing ectomycorrhizal roots in soil from different horizons, irrespective of N addition. Most high‐throughput sequencing studies of these systems have concentrated on the fungi (Clemmensen et al ., ; Sterkenburg et al ., ; Kyaschenko et al ., ) or fungi and bacteria (Baldrian et al ., ) colonizing the upper organic soil horizons, although several earlier studies using older molecular methods have shown that the fungal communities are vertically stratified across different horizons (Dickie et al ., ; Rosling et al ., ; Lindahl et al ., ). Studies of bacterial stratification with respect to soil horizon are mostly confined to description of the communities inhabiting soil, rather than ectomycorrhizal roots (Eilers et al ., ; Turlapati et al ., ; Uroz et al ., ; Fransson and Rosling, ; Lopez‐Mondejar et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Pinus sylvestris is a widespread, economically important tree species in the globally extensive, boreal forest biome and known to associate with hundreds of fungal species forming ectomycorrhizal associations with its roots. Recent studies of fungi in pine forest soils using high-throughput sequencing (Kyaschenko et al, 2017) suggest that maintenance of ectomycorrhizal functional diversity may be important for mobilization of organic nutrient pools but were limited to the upper litter and humus and did not examine bacteria. Early microcosm studies of bacterial communities associated with soil colonized by ectomycorrhizal P. sylvestris roots (Heinonsalo et al (2001) examined horizon-related impacts on ectomycorrhizal fungi using morphotype-and RFLP-based analyses and substrate utilization profiles of associated bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This consensus mirrors some current models that parameterize ECM decay as a function of soil fertility (Orwin et al ., ; Franklin et al ., ; Baskaran et al ., ). At this time, however, relatively limited direct evidence exists to test these hypotheses under field settings (but see Lilleskov et al ., ; Sterkenburg et al ., ; Kyaschenko et al ., ). Intriguingly, Bödeker et al .…”
Section: Context‐dependence Of Ecm and Som Modificationmentioning
confidence: 99%